Polycystin 2 is increased in disease to protect against stress-induced cell death - Brill, Allison; Fischer, Tom Tobias; Walters, Jennifer M.; Marlier, Arnaud; Sewanan, Lorenzo R.; Wilson, Parker C.; Johnson, Eric K.; Moeckel, Gilbert; Cantley, Lloyd G.; Campbell, Stuart G.; Nerbonne, Jeanne M.; Chung, Hee Jung; et al. (Scientific reports, 2020)
Polycystin 2 (PC2 or TRPP1, formerly TRPP2) is a calcium-permeant Transient Receptor Potential (TRP) cation channel expressed primarily on the endoplasmic reticulum (ER) membrane and primary cilia of all cell and tissue types. Despite its ubiquitous expression throughout the body, studies of PC2 have focused primarily on its role in the kidney, as mutations in PC2 lead to the development of autosomal dominant polycystic kidney disease (ADPKD), a debilitating condition for which there is no cure. However, the endogenous role that PC2 plays in the regulation of general cellular homeostasis remains unclear. In this study, we measure how PC2 expression changes in different pathological states, determine that its abundance is increased under conditions of cellular stress in multiple tissues including human disease, and conclude that PC2-deficient cells have increased susceptibility to cell death induced by stress. Our results offer new insight into the normal function of PC2 as a ubiquitous stress-sensitive protein whose expression is up-regulated in response to cell stress to protect against pathological cell death in multiple diseases.